HUBUNGAN HIPERGLIKEMIA DENGAN TINEA KORPORIS PADA PASIEN DIABETES MELITUS TIPE 2 DI RUMAH SAKIT GRAHA HERMINE BATAM TAHUN 2021 - Sudarsono, Sudarsono; Ipaljri, Andi; Shaleha, Niswatun (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2023)
Background: Tinea corporis or also known as ringworm, is a superfisial fungal infection of The skin that can effect people of all ages and genders. Hyperglycemia is a risk factor for tinea corporis in diabetic patients (especially type 2 diabetes mellitus), so that glycemic control plays an important role in The prevention and management of this condition. This study aims to determine the relations between hyperglycemia and tinea corporis in type 2 diabetes mellitus patients at Graha Hermine Hospital Batam in 2021. Methods: This study is an observational analytic study with a cross-sectional design in 71 type 2 diabetes mellitus patients visiting Graha Hospital Hermine Batam in 2021 which was selected using the purposive sampling method. Data is secondary data derived from medical records. Data analysis was performed with The Fisher statistical test. Results: The average age of the research respondents was in the 46-55 year group and based on the gender of the respondents in this study, 52.1% were male and 47.9% female. As many as 57.7% of respondents experienced hyperglycemia and 7.0% experienced tinea corporis. There is no relationship between hyperglycemia and the incidence of tinea corporis in diabetes mellitus patients at Graha Hermine Hospital Batam in 2021 (p=0,644). Conclusion: There is no relationship between hyperglycemia and the incidence of tinea corporis in diabetes mellitus patients at Graha Hermine Hospital Batam in 2021.